Assistance in Simple Financial Preparation and the Use of E-Peken for MSMEs in Pakal Subdistrict: Pendampingan Penyusunan Keuangan Sederhana Dan Penggunaan E-Peken Pada UMKM Kecamatan Pakal - Novita Ramadhani Sukma Cahyanti; Sugeng Purwanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
This activity aims to assist MSMEs in Pakal Subdistrict in preparing simple financial reports and optimizing the use of the E-Peken platform to improve financial management and market access. The method used is an action research approach involving problem identification, assistance, implementation and mentoring, and evaluation. The results of the mentoring program indicate that the assistance successfully enhanced the MSMEs ability to prepare simple financial reports, understand and utilize the features of E-Peken, and improve market access and revenue. This assistance provides recommendations for the government and related stakeholders in encouraging the development of MSMEs through mentoring programs and the use of digital technology.